A Four‐Armed Unsymmetrical Cryptand: From Two Different Host–Guest Interactions to Responsive Supramolecular Polymer. Issue 1 (31st July 2017) - Yao, Chenhao; Zhang, Jing; Cheng, Ming; Sun, Qiang; Pan, Yi; Jiang, Juli; Wang, Leyong
Abstract: By linking BMP32C10 and DB24C8 motifs together, a four‐armed cryptand 1 is synthesized successfully, in which BMP32C10 motif can bind paraquat 2 while DB24C8 motif can complex dibenzylammonium salt 3 in spite of the electrostatic repulsion between guests 2 and 3 . The base/acid‐responsive supramolecular polymer is constructed further via two kinds of host–guest interactions between cryptand 1 and two homoditopic paraquat 4 and dibenzylammonium salt 5 similar to guests 2 and 3 . Abstract : A four‐armed cryptand containing BMP32C10 and DB24C8 motifs is synthesized, which can bind a paraquat and dibenzylammonium salt via two kinds of interactions at the same time. The pH‐responsive supramolecular polymer is constructed further among a cryptand and two homoditopic guests.